Peri-Loss Dissociation and Psychotic like symptoms in a female patient: a rare presentation (GAIMS Journal of Medical Sciences, 2022)
Bereavement is a severe stressor that typically incites painful and debilitating symptoms of acute grief that commonly progress to restoration of a satisfactory, if changed, life. Complicated Grief is a bereavement specific syndrome characterized by traumatic and separation distress lasting over 6 months. A little is known about the role of dissociative experience during or immediately after the loss of loved one in Complicated Grief. Peri-Loss Dissociation may be useful in identifying individuals at risk for Complicated Grief and its relationship with treatment outcomes for different treatment approaches.